Relationship of early weaning and non-nutritive sucking habits with facial development - Erum Behroz Khan; Ayesha Bibi; Hunny; Danish Ali Mottani; Sarvaich Kumar (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of malocclusion features, convex facial profile and non-nutritive sucking habits among children with and without early weaning. Methods: The cross-sectional study was conducted at the National Institute of Child Health, Karachi, from June to December 2020, and comprised of either gender aged 3-6 years. The subjects were clinically examined, and details of lactation period, bottle feeding, thumb and pacifiers sucking were gathered from the parents to assess association with malocclusion. Data was analysed using SPSS 20. Results: Of the 180 subjects, 100(55.5%) were boys and 80(45.5%) were girls. There was significant association of early weaning with non-nutritive sucking habits, absent primate spaces, deviated midlines, and complete overbite (p<0.05). Breastfeeding <2 years was significantly associated with anterior crossbite (p<0.05). Early weaning had no association with convex facial profile, distoclusion, anterior and posterior crossbite and increased overjet (p>0.05). Non-nutritive sucking habits had significant relationship with deviated dental midlines (p>0.05). Conclusion: Early weaning was found to be a factor in establishing non-nutritive sucking habits, and was strongly associated with crowding, disturbed vertical overlapping of incisors and developing decreased facial height. Breastfeeding for less than the recommended duration had a tendency to lead to anterior cross-bite. Key Words: Weaning, Non-nutritive sucking habits, Malocclusion, Crowding, Overbite.